A THREE STEP B2B SALES MODEL BASED ON SATISFACTION JUDGMENTS - Grünbaum, Niels Nolsøe (European Scientific Journal, ESJ, 2015)
This paper aims to provide a coherent, detailed and integrative understanding of the mental processes (i.e. dimensions) that industrial buyers apply when forming satisfaction judgments in adjacent to new task buying situations. A qualitative inductive research strategy is utilized in this study. The insights produces can be applied for selling companies to craft close collaborative customer relationships in a systematic ad efficient way. The process of building customer relationships will be guided through actions that yields higher satisfaction judgments leading to loyal customers and finally to increase in sales and profitability. The specific nature of the developed insight will further make it difficult for competitors‘ to copy. Thus, processing the guidelines offered by the proposed typology in a successful manner will have the potential to create unique competitive advantages form the selling companies‘ perspective. The buying center members applied satisfaction dimension when forming satisfaction judgments. Moreover, the focus and importance of the identified satisfaction dimensions fluctuated pending on the phase of the buying process. Based on the findings a three step sales model is proposed comprising of 1. Identification of the satisfaction dimensions the buying center members apply in the buying process. 2. Identification of the fluctuation in importance of the satisfaction dimensions and finally 3. Identification of the degree of expectations‘ adjacent to the identified satisfaction dimensions.